Rancangan Penerapan Lean Service Di Departemen Service Control Guna Meningkatkan Pelayanan Terhadap Pelanggan Internal Di Gedung Kantor Pusat Pt Xyz Tbk - Meilan Agustin (Sekolah Tinggi Teknik - PLN, 2016)
The application of lean concepts in manufacturing have often heard success. And it should also be used in service industry. The use of lean concept was expected to make the process of work will more effective and efficient. The purpose of this study was to analyze and propose improvements to work processes that have been conducted so far, so it will obtain a series of work within their lean principles, namely: value, value stream, flow, pull, and continuous improvement. One main task of the Service Control at PT. XYZ Tbk was the handling of complaints about the comfort of the employees in the work. Based on data for the year 2011, complaints regarding power supply (lighting) reached 53.2%. Based on the mapping process carried out on the handling of complaints lighting problem, obtained the total time it takes as much as 109 minutes. To capture the value of internal customers, distributed questionnaires to 50 respondents. The selected sample is the department that is in the halls of PT XYZ Tbk are then represented by a person who assessed understanding of the complaint process. After improvement with lean concepts, the completion time of the complaint obtained change lamp replacement to 58 minutes, or increased by 53.2%.